-7n-33=n+3(5n+3)

Simple and best practice solution for -7n-33=n+3(5n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n-33=n+3(5n+3) equation:



-7n-33=n+3(5n+3)
We move all terms to the left:
-7n-33-(n+3(5n+3))=0
We calculate terms in parentheses: -(n+3(5n+3)), so:
n+3(5n+3)
We multiply parentheses
n+15n+9
We add all the numbers together, and all the variables
16n+9
Back to the equation:
-(16n+9)
We get rid of parentheses
-7n-16n-9-33=0
We add all the numbers together, and all the variables
-23n-42=0
We move all terms containing n to the left, all other terms to the right
-23n=42
n=42/-23
n=-1+19/23

See similar equations:

| 21+t=1 | | 7.26a+7a=-2.74+5a | | 4x+6/5=8x-8/6 | | (1/3)x+2=x-4 | | -9y-15-2y=7 | | 3x+12=7x+88 | | 5(8y)5(-2)=150 | | 31/4x+91/2=181/6 | | (x-2)(x-2)=11x-4 | | 9w+14=122 | | -12+6e=-30 | | (x-35)+1/2x+(x-46)+x=180 | | x=-(-4)+-3 | | 50=18-4x | | 0.25q+0.25(q-4)=17.50 | | -2u+16=-7u+6 | | x*2-7=15 | | -4(2x-3)-2x=10 | | 2/5x^+7=17 | | 3x^2-8=25 | | 5w-7=12-5w | | 5x^/4-4=16 | | -1/2-1/3v=-2/7 | | 65+(x+-5)+x=180 | | 3x-3(-2x-10)=-15 | | 41/2+w=61/2 | | 2(3x+8)=-38+6 | | 5n+2=16-2n | | 3+a/4=10 | | 10/2.2=15/n | | -3v-3+7v=4v+1-7 | | 10/2.2=15/m |

Equations solver categories